Public budgeting: good practices budgeting in oil and gas industry - Mohd Yusof, Muhammad Suhaimi; Romle, Abd Rahim; Mohd Kamal, Khirul Azwan; Yusof, Nur Ain; Othman, Sarimah; Azidin, Siti Sarah (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
Background: Oil and gas is destined to be as giant missions since it encompassing multiple business units, many resources, huge numbers of workers and suppliers and it required big budgets that go with them. Public budgeting is a field of public administration while the budgeting is characterized by its approaches, functions, formation and type. According to the [5], the function of the budget is “...budgets are used to filter and analyze information throughout the organization, not necessarily to create more information for dissemination…” while on the strategic level, “…budgeting clarifies its competitive priorities, advantages and strategies for the future, employing cost forecasts and demand limits to quantitatively measure the feasibility of capital expansion projects..”, [16]. Public budgeting is a field of public administration while the budgeting is characterized by its approaches, functions, formation and type.